Satisfaction of tourists on museum visits in Melaka, Malaysia - Musa, Safiya (2012)
The tremendous impact of globalization on tourism brought structural changes that make heritage tourism an innovation in global phenomenon, that brings people closer to one another and encourage diversification of national economies. Malaysia has remarkable heritage that manifests itself in oral history, traditional music, dances and social practices which foster national revenue and economic developments. Museums in Melaka are among the heritage sites that attract national and international tourists to Malaysia every year. To maintain the tempo, one needs to examine the attributes of these museums that attract and satisfy the visitors. Several studies on the attributes of museums have been carried out to examine tourists’ satisfaction but little attention is paid to developing nations. Even the few researches conducted in Malaysia lack emphasis on investigating specifically, the attributes of museums in Melaka that could enhance satisfaction. This study investigates the tourists’ satisfaction with their visit to five selected museums in Melaka; comparing their expectations and perceptions, relationship between expectations and satisfaction and demographic and travel behaviour as these could influence satisfaction. The study collected 318 valid questionnaires analysed through SPSS to test the hypotheses and model developed from literature. The results showed significant gaps and strong relationship between tourists’ expectations, perceptions and satisfaction. It also indicated that tourists’ overall satisfaction depends on attractiveness and professionalism attributes while all other attributes were insignificant. The result further confirmed that attractiveness is strongly related to overall satisfaction while professionalism is weakly related. On tourists’ demography,nationality and level of education have strong relationship with overall tourists’ satisfaction. Finally, the study confirmed that visitors were not satisfied with some facilities for disables, children and the use of modern technology. The results have some implication on tourism industry, academics, tourists and policy makers. This study concludes that Melaka museum attractiveness and staff professionalism are most important attributes that lead to overall satisfaction.